Differences in the stylistic use of antonyms in the language of K. Karimov’s novel "Agabiy" - Go’beysinova Gu’lparshın Du’ysenbay qızı (Periodica Journal, 2023)
The article talks about the types of antonyms in the language of K. Karimov’s novel "Agabiy", and the meanings of the differences in their use
Keywords: novel language; language of; vocabulary tools